2019
DOI: 10.55016/ojs/ajer.v65i4.56587
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking as a Predictor of Self-Esteem of University Students

Seyithan Demirdag

Abstract: This study aimed to examine the predictive role of critical thinking on university students’ self-esteem. The participants of the study included 433 undergraduate students in a variety of programs. Of the 433 students, 294 were female while 139 male, and the mean age was 20.2 years. Data collection tools included the California Critical Thinking Scale and Coopersmith Self-Esteem Inventory. The relationship between the critical thinking and self-esteem of university students were determined using correlation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…The relation between self-esteem and academic performance has been analysed in the previous literature with mixed results [47]. Thus, for example, research by [48] or Vialle et al [49] reported that academic performance has no significant impact on selfesteem; both variables do not correlate.…”
Section: Self-esteem and Academic Performancementioning
confidence: 99%
“…The relation between self-esteem and academic performance has been analysed in the previous literature with mixed results [47]. Thus, for example, research by [48] or Vialle et al [49] reported that academic performance has no significant impact on selfesteem; both variables do not correlate.…”
Section: Self-esteem and Academic Performancementioning
confidence: 99%